A GluD Coming-Of-Age Story. Issue 3 (March 2017) - Yuzaki, Michisuke; Aricescu, A. Radu
Abstract : The GluD1 and GluD2 receptors form the GluD ionotropic glutamate receptor (iGluR) subfamily. Without known endogenous ligands, they have long been referred to as 'orphan' and remained enigmatic functionally. Recent progress has, however, radically changed this view. Both GluD receptors are expressed in wider brain regions than originally thought. Human genetic studies and analyses of knockout mice have revealed their involvement in multiple neurodevelopmental and psychiatric disorders. The discovery of endogenous ligands, together with structural investigations, has opened the way towards a mechanistic understanding of GluD signaling at central nervous system synapses. These studies have also prompted the hypothesis that all iGluRs, and potentially other neurotransmitter receptors, rely on the cooperative binding of extracellular small-molecule and protein ligands for physiological signaling. Trends: GluD1 and GluD2 were thought to be expressed preferentially in the inner ear and the cerebellum. Recent work has demonstrated that both GluD receptors are expressed in multiple brain regions, including the cerebral cortex and hippocampus. Human genetic studies also indicate their involvement in various neurodevelopmental and psychiatric disorders. Two extracellular endogenous ligands for GluD2 were identified in the cerebellum. Cbln1, released from and tethered to the presynaptic sites via neurexin, binds to the GluD2 amino-terminal domain (ATD).d -Serine, released from Bergmann glia, binds to the GluD2 ligand-binding domain (LBD). The transsynaptic triad of neurexin–Cbln1–GluD2 serves as a potent bidirectional synaptic organizer. Simultaneous binding ofd -serine to the LBD and Cbln1 to the ATD cooperate to induce GluD2 signaling leading to AMPA receptor endocytosis. This process is mediated by the cytoplasmic protein tyrosine phosphatase PTPMEG, which interacts with the C-terminal domain of GluD2.